Detecting and sonifying temporal patterns of body segments when batting - Kobayashi, A.; Nasu, D.; Morimoto, Y.; Kashino, M.; Kimura, T. (Proceedings, 2018)
To improve skill in sport activities it is essential to discern the temporal patterns of one`s own movements. Our previous motion capture experiment involving elite female softball players identified key differences in the temporal body movements between the top players and young players against fastballs/change-ups. In this paper, we found that key features could be extracted from the rotation of the pelvis and we developed a sonification feedback system with two nine-axes inertial sensors. Rotation patterns are converted into two synthesized sounds to represent the time at peak trunk rotation speed and impact time. We conducted a pilot experiment with this feedback proposal using expert and novice batters, male and female whether the participants can pace of the rotational motion in batting. As a result, this feedback approach may allow the user to alter the time of peak trunk rotation speed to more closely match the cue provided by the training sound.